â€œ STUDY OF THE IMPACT OF SAMARINDA WAREHOUSING ACTIVITIES ON UNSIGNALIZED INTERSECTIONS ON TEUKU UMAR ROAD - RAPAK INDAH SAMARINDA - EAST KALIMANTAN â€ - SANDY, TAUFIQ K (KURVA S JURNAL MAHASISWA, 2020)
Traffic jams occur in almost all cities, one of them is Samarinda City which is experiencing traffic jams every day. To overcome traffic congestion, adequate transportation facilities and infrastructure are needed. High mobility to carry out activities of daily life according to the availability of facilities and infrastructure that are safe, comfortable and smooth. One of the roads in Samarinda is the Teuku Umar Road, which is one of the important roads in the development of Samarinda, this road connects the city center with important places such as Samarinda City Warehousing, Government offices such as the House of Representatives (DPRD) ) Samarinda City also connects to shopping places such as Big malls, and others. Where the traffic activity is quite high with a variety of motorized vehicles both private vehicles, public transport and heavy vehicles that every day crowded the road, with the Warehouse complex in Samarinda, Warehousing activities will have an impact on the performance of the surrounding road network including the No Junction signaled on the street Teuku Umar - Rapak Indah, as well as the impact on people who are disturbed from the activity of getting in and out of vehicles from Warehousing, decreasing vehicle speed, will even provide a large enough pull that will have an impact on the volume of traffic in the morning, afternoon, evening or during rush hours . ✓ Image of an unsigned intersection floor plan on the Teuku umar - Rapak Indah road with additional distance to turn ✓ Peak Hour Factor (PHF) value of 0.93 ✓ The capacity (C) of the intersection is 2538 pcu / hour ✓ Saturation Degree (DS) value is 1,391.